GENE ACTION IN THE INHERITANCE OF AGRONOMIC TRAITS ININTER VARIETAL DIALLEL CROSSES OF GOSSYPIUM HIRSUTUM L. - S. B. Hussain; M. Javed; M. Zubair; N. Ahmad (Journal of Animal and Plant Sciences, 2013)
5 × 5 complete diallel cross experiment was accomplished having cotton varieties CIM-556, CIM-557, NIBGE-2, Bt- Aone and CIM-786 to estimate gene action, general and specific combining ability for numerous plant traits involving yield and lint characters. The analysis of variance displayed highly significant differences amongst genotypes for all the traits under examination. The outcomes of joint regression analysis discovered that the data for all the traits were adequate for simple additive dominance model. The graphical representation of variance (Vr) and co-variance (Wr) proposed additive gene action with partial dominanceaction. The variety CIM-556 carried maximum dominant genes for seed index and fiber length although variety CIM-786 possessed supreme dominant genes for number of bolls and fiber fineness. The varieties NIBGE-2 and CIM-557 have dominant genes for fiber strength and lint percentage respectively. The variety CIM-786 was bringing into being best general combiner for seed cotton yield and seed index. The variety Bt- Aone appeared to be good general combiner for seed cotton yield. The variety CIM-556 inspected to be most promising general combiner for lint percentage and fiber length. Bt-Aoneexecuted very well in specific crosses with NIBGE-2 and CIM-786 for fineness. It was proposed that the plant traits involving additive type of gene action in their inheritance pattern, simple selection procedure would be convenient for their improvement while characters involving over dominance type of gene action might be considered when heterosis is to be exploited in cotton variety development program.
Keywords: Gossypiumhirsuitum L; gene action; specific combining ability; general combiningability; agronomic traits